Mechanically durable green aerogel composite based on agricultural lignocellulosic residue for organic liquids/oil sorption. (July 2022) - Chhajed, Monika; Verma, Chhavi; Sathawane, Manoj; Singh, Shiva; Maji, Pradip K.
Abstract: Various oil spill cleanup sorbents have good hydrophobicity and oil separation efficiency, but their practical use has been limited due to the difficult and costly fabrication procedure. The research aims towards material development using the consumption of lignocellulosic agricultural residue for isolating cellulose nanofiber and its forward use to construct a 3D porous structure. A simple freeze-drying technique was used to assemble low-density porous structure. The biodegradable polylactic acid coating was used to alter the wettability from hydrophilic to hydrophobic and the maximum water contact angle value was around 120°. The prepared coated samples were testified for a series of oil/organic solvents-water mixtures. The sorption capacity was in the range of 28–70 g/g. The prepared aerogels were efficiently reused for at least 10 cycles. Developed material was used in continuous oil-water separation to remove oil from the water's surface. The cost analysis was estimated for scaleup production in the future. Graphical abstract: Unlabelled Image Highlights: The lightweight porous aerogel was derived fro lignocellulosic agriculture waste. Simple polylactic acid (PLA) coating was used to impart the hydrophobicity. The aerogel was effectively absorbing oil/organic solvent by 70 g/g of its own weight. The aerogel was able to clean the oil/organic spill from water in continuous manner. The tentative cost and energy analysis has also been investigated.